2004
DOI: 10.2307/3552523
|View full text |Cite
|
Sign up to set email alerts
|

Access to College and University: Does Distance to School Matter?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 6 publications
6
89
0
2
Order By: Relevance
“…Frenette (2004) finds support for the idea that increased distance to school is associated with lower university attendance and a larger tendency to attend the local college. This relationship is found to be much stronger in lower-income families.…”
Section: Educational Systemmentioning
confidence: 77%
“…Frenette (2004) finds support for the idea that increased distance to school is associated with lower university attendance and a larger tendency to attend the local college. This relationship is found to be much stronger in lower-income families.…”
Section: Educational Systemmentioning
confidence: 77%
“…Although a few studies have investigated student behaviours by using distance between higher education institutions as an input variable (e.g. Frenette 2004;Denzler and Wolter 2011), little is known about the influence distance between institutes with identical programmes on attractiveness of programmes. Using a data set from the Dutch Ministry of Education ('Dienst Uitvoering Onderwijs') consisting of students from 1356 study programmes spread across 50 institutions within the period of 2008-2013, this study has investigated the relationship between higher education institutes' study programme and distance included competition, programme variety and other characteristics such as gender among the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of distance variables on attractiveness of higher education institutions have been widely discussed, relatively little has been identified about whether and how distance affects the choice of a programme. A previous study analysing the relationship between distance and university choice showed that there is a strong negative relationship between the two (Frenette 2004). Apart from this, some economic studies used distance-to-university as an exogenous variable in their estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Für den nordamerikanischen Raum existieren einige Studien, die zeigen, dass die Entfernung zur nächsten Hochschule die Aufnahme eines Studiums negativ beeinflusst (Card 1995;Frenette 2004Frenette , 2006Turley 2009 Sá et al (2004). C (costs), Erträge B (benefits) und die Erfolgswahrscheinlichkeit P (probability of success) alternativer Bildungswege und wählen die Option mit dem größten Nutzen U (utility) aus (Erikson & Jonsson 1996: 13 ff.…”
Section: Theoretischer Rahmenunclassified